Tipologi Fungsi dan Makna Ala dalam Al-Qur’an Berdasarkan Analisis Semantik Kontekstual - M. Sholahuddin Al Ayyubi (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study examines the typology of the function and meaning of the particle ala in the Qur'an through the perspective of John Rupert Firth's Contextual Semantics. The study departs from the assumption that the meaning of ala is relational and contextual, not lexical and fixed. Using a qualitative approach and descriptive-analytical methods, this study aims to map the variations in meaning and function of this particle by analyzing collocation patterns and situational contexts in each instance of its occurrence. The results show that ala functions as an active discourse marker whose meaning is dynamically shaped by its linguistic and context of situation. Based on Firthian analysis, a typology of the functions of ala was produced into four main categories: (1) exhortative function, (2) logical emphasis function, (3) serious warning function, and (4) rejection function. Each function correlates with specific collocational and situational contexts, such as its relationship with verses of punishment, arguments of tawhid, or the spread of da'wah. The conclusion of the study confirms that the meaning of ala is relational and contextual, rather than lexical and fixed. These findings not only provide a systematic functional map for understanding ala, but also offer an analytical model that can be applied to other micro-linguistic elements in the Qur'an.